Modified lithium iron manganese phosphate positive electrode material and preparation method thereof, positive electrode and battery
By doping selenium or tellurium into the lithium manganese ferrophosphate positive electrode material, forming Se-O bonds or Te-O bonds, and performing secondary phosphorus replenishment, the problem of Mn ion dissolution in the LFMP positive electrode material is solved, and the cycle stability is significantly improved and electronic conductivity, achieving efficient lithium-ion battery cycling performance.
Patent Information
- Application Number
- CN202411528798.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
AI Technical Summary
The dissolution problem of Mn ions in lithium iron manganese phosphate (LFMP) cathode materials leads to degradation of cyclic performance and attenuation of electrochemical performance, and the prior art has failed to effectively solve this problem.
By doping selenium (Se) or tellurium (Te) into the lithium manganese ferrophosphate positive electrode material, the phosphorus elements in part of the phosphate are replaced, and the Se-O bond or Te-O bond is formed, and the main elements are fine-tuned after secondary phosphorus replenishment is fine-tuned. P content improves particle sphericality and electronic conductivity.
The cyclic stability of the positive electrode material is significantly improved, the dissolution of Mn ions is reduced, and the electron conductivity and cycling performance are improved. The 1C charging capacity and discharge capacity are significantly improved. The capacity retention rate after 500 cycles reaches more than 99.9%.
Smart Images

Figure CN119419239A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a modified lithium manganese iron phosphate positive electrode material and a preparation method thereof, a positive electrode and a battery. Background Art
[0002] Lithium iron manganese phosphate (LFMP) cathode material is the next generation cathode material of the existing lithium iron phosphate (LFP) cathode material. The biggest difference between it and LFP is that Mn ions replace some Fe ions in the crystal structure. This change not only increases the operating voltage of the LFMP cathode (2.0V~4.3V), but also changes the conduction dynamics of Li ions in the cathode material. Therefore, compared with LFP material, LFMP has a higher capacity, a higher capacity retention rate, and significantly improved low-temperature performance.
[0003] However, LFMP has a fatal disadvantage, that is, Mn ions will undergo redox reactions in a higher voltage range and dissolve from the positive electrode material. This phenomenon will not only significantly reduce the cycle performance of LFMP, but also have a great impact on the storage and gas production of the battery cell. How to effectively solve the problem of Mn ion dissolution in LFMP has become a severe scientific and engineering obstacle.
[0004] Currently, there is no effective means to improve the dissolution of Mn ions in LFMP, and new solutions still need to be further explored. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a modified lithium iron manganese phosphate positive electrode material and a preparation method thereof, a positive electrode and a battery, which can effectively improve the dissolution of Mn ions in LFMP, thereby significantly improving the cycle stability of the positive electrode material and avoiding the technical problem of easy attenuation of electrochemical performance; at the same time, secondary phosphorus supplementation is carried out to fine-tune the content of the main element P and adjust the proportion of PO bonds, so that the sphericity of the LFMP particles is better and the compaction density is higher.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a modified lithium iron manganese phosphate positive electrode material, wherein the modified lithium iron manganese phosphate positive electrode material comprises a core and a coating layer located on the surface of the core, wherein the chemical formula of the core comprises Li x Mn y Fe 1-y D z P 1-z O4(P h ), D is selected from Se and / or Te; wherein, 1≤x≤1.05, 0.2≤y≤0.8, 0.01≤z≤0.055, 1.001<1-z+h≤1.055.
[0008] In the present invention, "(P h )" refers to the additionally supplemented P element.
[0009] It is worth noting that the lithium iron manganese phosphate material often causes structural damage due to the problem of manganese dissolution, and the resistivity also increases accordingly, affecting the electrochemical cycle stability. The modified lithium iron manganese phosphate positive electrode material provided by the present invention is doped with Se and / or Te in the lithium iron manganese phosphate, and the lithium ion diffusion channel is widened by the addition of Se and / or Te, the lithium ion diffusion rate is increased, and the lithium ion conductivity of the positive electrode material is improved. Se and / or Te are doped into phosphate to replace P elements and O to form Se-O bonds and Te-O bonds, wherein the presence of Se-O bonds and Te-O bonds can improve the stability and electronic conductivity of the positive electrode material to a certain extent, and further limit the volume expansion of the positive electrode material; and the additionally supplemented P element can further increase the particle sphericity of the positive electrode material, improve the stability of the positive electrode material structure, and reduce the instability of manganese in the system, thereby causing the problem of easy attenuation of electrochemical performance.
[0010] In the present invention, Se and / or Te are selected to replace part of P. Compared with the P element, Se / Te has the advantages of improving the stability and electronic conductivity of the positive electrode material.
[0011] Among them, 1≤x≤1.05, for example, it can be 1.00, 1.01, 1.02, 1.03, 1.04 or 1.05.
[0012] 0.2≤y≤0.8, for example, it can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8, etc.
[0013] 0.01≤z≤0.055, for example, it can be 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045, 0.05 or 0.055, etc.
[0014] The selection of z in the present invention is required to be within the above range. When the value of z is too large, it is easy to produce impurity phases and affect the stability of the material structure. When the value of z is too small, it is easy to have a problem that the effect of doping to improve stability is not obvious.
[0015] 1.001<1-z+h≤1.055, for example, it can be 1.001, 1.007, 1.013, 1.019, 1.025, 1.031, 1.037, 1.043, 1.049 or 1.055, etc.
[0016] Preferably, the D50 of the modified lithium manganese iron phosphate positive electrode material is 90nm to 170nm, for example, it can be 90nm, 99nm, 108nm, 117nm, 126nm, 135nm, 144nm, 153nm, 162nm or 170nm.
[0017] Preferably, the average sphericity of the modified lithium manganese iron phosphate positive electrode material is ≥0.80, for example, it can be 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.88, 0.89, 0.90, 0.91, 0.92, 0.98, 0.99 or 1, etc.
[0018] Preferably, the coating layer is a P and C co-doped carbon layer.
[0019] Preferably, the coating layer has a thickness of 0.2 nm to 3 nm, for example, 0.2 nm, 0.6 nm, 0.9 nm, 1.2 nm, 1.5 nm, 1.8 nm, 2.1 nm, 2.4 nm, 2.7 nm or 3 nm.
[0020] Preferably, the carbon content in the modified lithium manganese iron phosphate positive electrode material is 1.4wt% to 1.8wt%, for example, it can be 1.4wt%, 1.45wt%, 1.49wt%, 1.54wt%, 1.58wt%, 1.63wt%, 1.67wt%, 1.72wt%, 1.76wt% or 1.8wt%, etc.
[0021] Preferably, the modified lithium manganese iron phosphate positive electrode material includes Se-O bonds and / or Te-O bonds, and the content of the Se-O bonds and / or Te-O bonds is 0.35% to 1.67%, for example, it can be 0.35%, 0.36%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.48%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.5%, 1.6% or 1.67%, etc. In the present invention, the content of Se-O bonds and / or Te-O bonds is required to be within the above range. When the content of Se-O bonds and / or Te-O bonds is too large, the problem of impurity phases affecting the stability of the material structure is likely to occur. When the content of Se-O bonds and / or Te-O bonds is too small, the problem of insignificant effect of doping to improve stability is likely to occur.
[0022] Preferably, the modified lithium manganese iron phosphate positive electrode material includes PO bonds and Li-O bonds. The content of the PO bonds is 36.27% to 38.23%, for example, it can be 36.27%, 36.3%, 36.4%, 36.8%, 36.9%, 37.0%, 37.1%, 37.2%, 37.35%, 37.5%, 37.8%, 38.0%, 38.1%, 38.2% or 38.23%, etc. The content of the Li-O bonds is 3.1% to 3.3%, for example, it can be 3.1%, 3.11%, 3.12%, 3.13%, 3.14%, 3.15%, 3.18%, 3.2%, 3.22%, 3.23%, 3.24%, 3.25%, 3.28% or 3.3%, etc. The selection of the PO bond content in the present invention is required to be within the above range. When the PO bond content is too high, the material particles are likely to be too large and impurity phases are generated. When the PO bond content is too low, the particles are likely to be too small and the sphericity is low. The selection of the Li-O bond in the present invention is required to be within the above range. When the Li-O bond content is too high, the material pH is likely to be too high and the particles are likely to be too small. When the Li-O bond content is too low, the battery capacity is likely to be insufficient.
[0023] It is worth noting that the bond content in the present invention refers to the ratio of the number of a certain bond in a compound to the total number of all bonds in the compound. For example, the PO bond content refers to the ratio of the number of PO bonds to the total number of all bonds detected in the finished product of lithium manganese iron phosphate.
[0024] Preferably, the full width at half maximum (FWHM) of the X-ray diffraction spectrum of the modified lithium manganese iron phosphate positive electrode material is 0.157 to 0.179, for example, it can be 0.157, 0.16, 0.162, 0.165, 0.167, 0.17, 0.172, 0.175, 0.177 or 0.179, etc. In the present invention, the FWHM value is within the above range. When the FWHM is too large, the problem of poor ion and electron conductivity is likely to occur. When the FWHM is too small, the problem of affecting the performance and charge and discharge efficiency of the battery is likely to occur.
[0025] In a second aspect, the present invention provides a method for preparing the modified lithium manganese iron phosphate positive electrode material according to the first aspect, the preparation method comprising the following steps:
[0026] (1) mixing a carbon source, a lithium source, an iron source, a manganese source, a D source and a phosphorus source according to a molar ratio of molecular formula A, grinding and drying to obtain a precursor; wherein molecular formula A is Li x Mn y Fe 1-y D z P 1-zO4, the D source includes at least one of a selenium source and a tellurium source; wherein 1≤x≤1.05, 0.2≤y≤0.8, 0.01≤z≤0.055;
[0027] (2) The precursor of step (1) is subjected to a first sintering to obtain a first sample;
[0028] (3) Mixing a supplementary phosphorus source, a carbon source and the first sample of step (2), and grinding and sintering them in sequence to obtain the modified lithium manganese iron phosphate positive electrode material.
[0029] In the present invention, a lithium source, an iron source, a manganese source, a D source and a phosphorus source are first mixed according to molecular formula A, and the D source includes a selenium source and / or a tellurium source, so that a Se-O bond is formed between Se and O, and a Te-O bond is formed between Te and O. The presence of the Se-O bond and the Te-O bond can improve the stability and electronic conductivity of the positive electrode material to a certain extent, and further limit the volume expansion of the positive electrode material. At the same time, the content of the main element P is fine-tuned in combination with secondary P supplementation, and the PO bond is increased to make the particle sphericity better. At the same time, the P element is combined with the outer carbon to improve the electronic conductivity of the material, reduce manganese dissolution, and reduce the manganese dissolution from 17 mg / L to 0 mg / L, thereby improving the electronic conductivity and the cycle performance.
[0030] Preferably, the lithium source in step (1) comprises any one or a combination of at least two of lithium carbonate, lithium hydroxide, lithium nitrate, lithium formate, lithium silicate, lithium sulfate, lithium phosphate, lithium oxalate, lithium octanoate, lithium citrate, lithium salicylate, lithium orthosilicate, lithium permanganate, lithium trifluoroacetate, lithium acetoacetate, lithium difluorophosphate, lithium hexafluorophosphate, lithium benzoate, lithium metaphosphate, lithium pyruvate, lithium acetate, lithium fluoride, lithium bromide, lithium methoxide, lithium ethoxide, lithium oxide, lithium nitride or lithium sulfide, wherein a typical but non-limiting combination is The invention relates to a combination of lithium carbonate and lithium hydroxide, a combination of lithium nitrate and lithium hydroxide, a combination of lithium formate and lithium nitrate, a combination of lithium formate and lithium hydroxide, a combination of lithium silicate and lithium hydroxide, a combination of lithium carbonate and lithium sulfate, a combination of lithium acetoacetate and lithium hydroxide, a combination of lithium difluorophosphate and lithium hydroxide, a combination of lithium bromide and lithium ethoxide, a combination of lithium fluoride and lithium pyruvate, a combination of lithium carbonate and lithium pyruvate, a combination of lithium oxide and lithium hydroxide, a combination of lithium carbonate and lithium sulfide, and a combination of lithium metaphosphate and lithium hydroxide.
[0031] Preferably, the iron source comprises any one of ferrous oxalate, ferrous nitrate, ferrous sulfide, ferrous sulfate, ferrous phosphate, ferrous iodide, ferrous fluoride, ferrous bromide, ferrous acetylacetonate, ferrous gluconate, ferrous chloride or ferrous acetate, or a combination of at least two thereof, wherein a typical but non-limiting combination is a combination of ferrous oxalate and ferrous nitrate, a combination of ferrous sulfide and ferrous nitrate, a combination of ferrous oxalate and ferrous sulfide, a combination of ferrous phosphate and ferrous nitrate, a combination of ferrous oxalate and ferrous iodide, a combination of ferrous fluoride and ferrous iodide, a combination of ferrous oxalate and ferrous fluoride, a combination of ferrous bromide and ferrous iodide, a combination of ferrous acetylacetonate and ferrous iodide, and a combination of ferrous acetylacetonate and ferrous gluconate.
[0032] Preferably, the manganese source comprises any one of manganese dioxide, manganese oxalate, manganese acetate, manganese carbonate, manganese phosphate, manganese sulfate or manganese nitrate, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of manganese dioxide and manganese oxalate, a combination of manganese acetate and manganese oxalate, a combination of manganese dioxide and manganese acetate, a combination of manganese carbonate and manganese oxalate, a combination of manganese dioxide and manganese carbonate, a combination of manganese phosphate and manganese carbonate, a combination of manganese dioxide and manganese phosphate, a combination of manganese sulfate and manganese phosphate, and a combination of manganese dioxide and manganese sulfate.
[0033] Preferably, the selenium source comprises any one or a combination of at least two of selenium dioxide, diselenide dichloride, selenium tetrachloride, selenium oxychloride, sodium selenite, orthoselenide (M2Se), acidic selenide (MSe) or phenylselenium chloride, wherein a typical but non-limiting combination is a combination of selenium dioxide and diselenide dichloride, a combination of selenium tetrachloride and diselenide dichloride, a combination of selenium dioxide and selenium tetrachloride, a combination of sodium selenite and diselenide dichloride, a combination of selenium dioxide and sodium selenite, a combination of acidic selenide and sodium selenite, and a combination of acidic selenide and phenylselenium chloride. Wherein M represents a metal element.
[0034] Preferably, the tellurium source comprises any one or a combination of at least two of tellurium powder, sodium tellurite, potassium tellurite, copper telluride, zinc telluride or telluric acid, wherein typical but non-limiting combinations are a combination of tellurium powder and sodium tellurite, a combination of potassium tellurite and sodium tellurite, a combination of tellurium powder and potassium tellurite, a combination of copper telluride and zinc telluride, a combination of copper telluride and sodium tellurite, and a combination of zinc telluride and telluric acid.
[0035] Preferably, the phosphorus source comprises any one of ammonium hypophosphite, ammonium polyphosphate, diammonium phosphate, diammonium hydrogen phosphate, ammonium hexafluorophosphate, ammonium phosphate, phosphoric acid or pyrophosphoric acid, or a combination of at least two thereof, wherein a typical but non-limiting combination is a combination of ammonium hypophosphite and ammonium polyphosphate, a combination of diammonium phosphate and ammonium polyphosphate, a combination of ammonium hypophosphite and diammonium phosphate, a combination of diammonium hydrogen phosphate and ammonium polyphosphate, a combination of ammonium hypophosphite and diammonium hydrogen phosphate, a combination of ammonium hexafluorophosphate and diammonium hydrogen phosphate, a combination of ammonium hypophosphite and ammonium phosphate, and a combination of pyrophosphoric acid and diammonium hydrogen phosphate.
[0036] Preferably, based on the mass of the precursor, the amount of the carbon source added in step (1) is 7wt% to 9wt%, for example, it can be 7wt%, 7.3wt%, 7.5wt%, 7.7wt%, 7.9wt%, 8.2wt%, 8.4wt%, 8.6wt%, 8.8wt% or 9wt%, etc.
[0037] Preferably, the first sintering includes heating to a first sintering temperature at a first heating rate and then holding the temperature for the first sintering.
[0038] Preferably, the first heating rate is 1-5°C / min, for example, it can be 1°C / min, 1.5°C / min, 1.9°C / min, 2.4°C / min, 2.8°C / min, 3.3°C / min, 3.7°C / min, 4.2°C / min, 4.6°C / min or 5°C / min, etc.
[0039] Preferably, the first sintering temperature is 300-500°C, for example, it may be 300°C, 323°C, 345°C, 367°C, 389°C, 412°C, 434°C, 456°C, 478°C or 500°C.
[0040] Preferably, the first sintering and heat-keeping time is 6 to 10 hours, for example, it can be 6 hours, 6.5 hours, 6.9 hours, 7.4 hours, 7.8 hours, 8.3 hours, 8.7 hours, 9.2 hours, 9.6 hours or 10 hours.
[0041] Preferably, based on the first sample, the amount of the supplementary phosphorus source added is 0wt% to 5.5wt%, for example, it can be 0wt%, 0.7wt%, 1.3wt%, 1.9wt%, 2.5wt%, 3.1wt%, 3.7wt%, 4.3wt%, 4.9wt% or 5.5wt%, etc.
[0042] Preferably, the supplementary phosphorus source comprises any one of ammonium hypophosphite, ammonium polyphosphate, diammonium phosphate, diammonium phosphate, ammonium hexafluorophosphate, ammonium phosphate, phosphoric acid or pyrophosphoric acid, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of ammonium hypophosphite and ammonium polyphosphate, a combination of diammonium phosphate and ammonium polyphosphate, a combination of ammonium hypophosphite and diammonium phosphate, a combination of diammonium phosphate and ammonium polyphosphate, a combination of ammonium hypophosphite and diammonium phosphate, a combination of ammonium hexafluorophosphate and diammonium phosphate, a combination of ammonium hypophosphite and ammonium phosphate, and a combination of pyrophosphoric acid and diammonium phosphate.
[0043] Preferably, based on the first sample, the amount of the carbon source added in step (3) is 2wt% to 3wt%, for example, it can be 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt% or 3wt%, etc.
[0044] Preferably, the carbon source comprises any one of glucose, sucrose or polyethylene glycol or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of glucose and sucrose, a combination of polyethylene glycol and sucrose, a combination of glucose and polyethylene glycol, and a combination of polyethylene glycol, glucose and sucrose.
[0045] Preferably, the second sintering includes heating to a second sintering temperature at a second heating rate and then holding the temperature for the second sintering.
[0046] Preferably, the second heating rate is 1 to 10°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc.
[0047] Preferably, the second sintering temperature is 600-800°C, for example, it may be 600°C, 625°C, 645°C, 660°C, 680°C, 710°C, 730°C, 750°C, 770°C or 800°C.
[0048] Preferably, the second sintering and heat-keeping time is 6 to 8 hours, for example, it can be 6 hours, 6.3 hours, 6.5 hours, 6.7 hours, 6.9 hours, 7.2 hours, 7.4 hours, 7.6 hours, 7.8 hours or 8 hours.
[0049] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0050] (1) mixing a carbon source, a lithium source, an iron source, a manganese source, a selenium source and a phosphorus source according to a molar ratio of molecular formula A, grinding and drying to obtain a precursor; wherein molecular formula A is Li x Mny Fe 1-y D z P 1-z O4; wherein 1≤x≤1.05, 0.2≤y≤0.8, 0.01≤z≤0.055; based on the mass of the precursor, the amount of the carbon source added is 7wt% to 9wt%;
[0051] (2) The precursor in step (1) is heated to a first sintering temperature of 300 to 500° C. at a first heating rate of 1 to 5° C. / min and kept at this temperature for 6 to 10 hours to obtain a first sample;
[0052] (3) mixing a supplementary phosphorus source, a carbon source and the first sample of step (2), grinding the mixture, and then heating the mixture to a second sintering temperature of 600 to 800° C. at a second heating rate of 1 to 10° C. / min and holding the mixture for 6 to 8 hours to obtain the modified lithium manganese iron phosphate positive electrode material;
[0053] Wherein, based on the mass of the first sample, the amount of the supplementary phosphorus source added in step (3) is 0wt% to 5.5wt%, and the amount of the carbon source added is 2wt% to 3wt%.
[0054] In a third aspect, the present invention provides a lithium-ion battery positive electrode, which comprises the modified lithium iron manganese phosphate positive electrode material described in the first aspect, and / or the modified lithium iron manganese phosphate positive electrode material obtained by the preparation method of the modified lithium iron manganese phosphate positive electrode material described in the second aspect.
[0055] The present invention has no special restrictions on the specific structure and other materials in the above-mentioned lithium ion battery positive electrode. Any structure and material that can be used for lithium ion positive electrode known to those skilled in the art can be adopted, and can also be adjusted according to actual conditions. For example, the positive electrode current collector is aluminum, etc. The conductive agent in the slurry preparation process can be one or more of carbon nanotubes, graphene, carbon black and carbon fibers, preferably one or more of carbon nanotubes, graphene and carbon black; the binder can be one or more of polyvinylidene fluoride PVDF, sodium carboxymethyl cellulose CMC, styrene butadiene rubber SBR, acrylonitrile multipolymer LA and polyacrylic acid PAA, preferably one or more of polyvinylidene fluoride PVDF, sodium carboxymethyl cellulose CMC and styrene butadiene rubber SBR; the solvent is one or more of N-methylpyrrolidone NMP, deionized water, acetone and dimethylacetamide DMAC, preferably one or more of N-methylpyrrolidone NMP, acetone and dimethylacetamide DMAC. The specific amount is selected according to the preparation of positive electrode sheets and lithium ion batteries in the art, and the amount added is not limited.
[0056] In a fourth aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the lithium ion battery positive electrode described in the third aspect.
[0057] The lithium ion battery positive electrode provided by the invention has excellent discharge capacity and cycle stability.
[0058] The present invention has no special restrictions on the specific structure and other materials in the above-mentioned lithium-ion battery. Any structure and material that can be used for lithium-ion batteries and is known to those skilled in the art can be used, and can also be adjusted according to actual conditions. For example, the electrolyte can be an ethylene carbonate solution of lithium hexafluorophosphate.
[0059] Compared with the prior art, the present invention has at least the following beneficial effects:
[0060] (1) The modified lithium iron manganese phosphate positive electrode material provided by the present invention can improve the stability of the positive electrode material structure, enhance the sphericity of the inner sphere particles, and reduce the problem of easy attenuation of electrochemical performance caused by the instability of manganese in the system by doping selenium and / or tellurium elements in the precursor synthesis, and replacing part of the phosphorus with selenium and / or tellurium.
[0061] (2) The modified lithium iron manganese phosphate positive electrode material provided by the present invention broadens the lithium ion diffusion channel by adding selenium and / or tellurium, increases the lithium ion diffusion rate, and improves the lithium ion conductivity of the positive electrode material.
[0062] (3) The preparation method of the modified lithium manganese iron phosphate positive electrode material provided by the present invention combines the secondary P supplementation to fine-tune the main element P content, increase the PO bond, and make the particle sphericity better. At the same time, the P element combines with the outer carbon to improve the electronic conductivity of the material, reduce manganese dissolution, improve electronic conductivity, and improve cycle performance. Under optimal conditions, the 1C charging capacity is above 151mAh / g, the 1C discharge capacity is above 141mAh / g, and the capacity retention rate after 500 cycles is above 99.9%, which basically does not decrease, and the application prospect is broad. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 This is a SEM image of the modified lithium manganese iron phosphate positive electrode material provided in Example 1 of the present invention.
[0064] Figure 2 This is an XRD comparison diagram of the modified lithium iron manganese phosphate positive electrode material provided in Example 1 of the present invention and the lithium iron manganese phosphate positive electrode material in Comparative Example 1. DETAILED DESCRIPTION
[0065] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0066] It should be understood that, in the description of the present invention, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0067] Example 1
[0068] This embodiment provides a method for preparing a modified lithium manganese iron phosphate positive electrode material, the preparation method comprising the following steps:
[0069] (1) lithium hydroxide, ferrous oxalate, manganese oxalate, selenium dioxide and ammonium dihydrogen phosphate are mixed in a molar ratio according to molecular formula A, 7 wt % of a carbon source (glucose) is added based on the mass of the precursor, and the mixture is ground and dried to obtain a precursor; wherein molecular formula A is Li 1.01 Mn 0.4 Fe 0.6 Se 0.02 P 0.98 O4;
[0070] (2) The precursor in step (1) is heated to a first sintering temperature of 500° C. at a first heating rate of 5° C. / min and held for 8 h to perform a first sintering to obtain a first sample;
[0071] (3) mixing 3% of the supplementary phosphorus source (ammonium dihydrogen phosphate), 2% of the carbon source (glucose) and the first sample of step (2) (the supplementary phosphorus source and the carbon source are based on the first sample), grinding, and then heating to a second sintering temperature of 700° C. at a second heating rate of 5° C. / min and holding for 8 hours to perform a second sintering, and then jet milling and pulverizing the material to obtain the modified lithium manganese iron phosphate positive electrode material Li 1.01 Mn 0.4 Fe 0.6 Se 0.02 P 0.98 O4(P 0.03 ).
[0072] The SEM image of the modified lithium manganese iron phosphate positive electrode material provided in this embodiment is as follows: Figure 1 As shown, from Figure 1 It can be seen that the positive electrode material particles of this embodiment are evenly distributed.
[0073] The XRD comparison diagram of the modified lithium manganese iron phosphate positive electrode material provided in Example 1 and the lithium manganese iron phosphate positive electrode material in Comparative Example 1 is as follows: Figure 2 As shown, from Figure 2It can be seen that the XRD peak of the modified lithium manganese iron phosphate positive electrode material in Example 1 is shifted compared with the traditional lithium manganese iron phosphate positive electrode material, and the half-peak full width changes significantly, indicating that the modification is successful.
[0074] Example 2
[0075] This embodiment provides a method for preparing a modified lithium manganese iron phosphate positive electrode material, the preparation method comprising the following steps:
[0076] (1) lithium citrate, ferrous acetylacetonate, manganese acetate, selenium oxychloride and pyrophosphate were mixed in a molar ratio according to molecular formula A, 7 wt % of a carbon source (glucose) was added based on the mass of the precursor, and the mixture was ground and dried to obtain a precursor; wherein molecular formula A is Li 1.01 Mn 0.3 Fe 0.7 Se 0.03 P 0.97 O4;
[0077] (2) The precursor in step (1) is heated to a first sintering temperature of 300° C. at a first heating rate of 1° C. / min and then kept at this temperature for 10 h to obtain a first sample;
[0078] (3) mixing 3.1% of a supplementary phosphorus source (ammonium dihydrogen phosphate), 2% of a carbon source (glucose) and the first sample of step (2) (the supplementary phosphorus source and the carbon source are based on the first sample), grinding, and then heating to a second sintering temperature of 800° C. at a second heating rate of 10° C. / min and holding for 6 hours to perform a second sintering, and then jet milling and pulverizing the material to obtain the modified lithium manganese iron phosphate positive electrode material Li 1.01 Mn 0.3 Fe 0.7 Se 0.03 P 0.97 O4(P 0.031 ).
[0079] Example 3
[0080] This embodiment provides a method for preparing a modified lithium manganese iron phosphate positive electrode material, the preparation method comprising the following steps:
[0081] (1) lithium oxalate, ferrous fluoride, manganese nitrate, selenium tetrachloride (C14Se) and diammonium hydrogen phosphate were mixed in a molar ratio according to molecular formula A, 7 wt % of a carbon source (glucose) was added based on the mass of the precursor, and the mixture was ground and dried to obtain a precursor; wherein molecular formula A is Li 1.01 Mn 0.4 Fe 0.6 Se 0.02 P 0.98 O4;
[0082] (2) The precursor in step (1) is heated to a first sintering temperature of 400° C. at a first heating rate of 3° C. / min and held for 6 hours to perform a first sintering to obtain a first sample;
[0083] (3) Mixing 5% of the supplementary phosphorus source (ammonium dihydrogen phosphate), 2.5% of the carbon source (glucose) and the first sample of step (2) (the supplementary phosphorus source and the carbon source are based on the first sample), grinding, and then heating to a second sintering temperature of 600° C. at a second heating rate of 1° C. / min and holding for 8 hours to perform a second sintering, and then jet milling and pulverizing the material to obtain the modified lithium manganese iron phosphate positive electrode material Li 1.01 Mn 0.4 Fe 0.6 Se 0.02 P 0.98 O4(P 0.05 ).
[0084] Example 4
[0085] This embodiment provides a method for preparing a modified lithium manganese iron phosphate positive electrode material, the preparation method comprising the following steps:
[0086] (1) lithium salicylate, ferrous bromide, manganese carbonate, telluric acid and ammonium hexafluorophosphate are mixed in a molar ratio according to molecular formula A, 7 wt % of a carbon source (sucrose) is added based on the mass of the precursor, and the mixture is ground and dried to obtain a precursor; wherein molecular formula A is Li 1.05 Mn 0.2 Fe 0.8 Te 0.01 P 0.99 O4;
[0087] (2) The precursor in step (1) is heated to a first sintering temperature of 450° C. at a first heating rate of 4° C. / min and held for 7 hours to perform a first sintering to obtain a first sample;
[0088] (3) mixing 4% of the supplementary phosphorus source (ammonium polyphosphate), 3% of the carbon source (graphene) and the first sample of step (2) (the supplementary phosphorus source and the carbon source are based on the first sample), grinding, and then heating to a second sintering temperature of 750° C. at a second heating rate of 2° C. / min for a second sintering and holding for 6.5 h to perform a second sintering, and then jet milling and pulverizing the material to obtain the modified lithium manganese iron phosphate positive electrode material Li 1.05 Mn 0.2 Fe 0.8 Te 0.01 P 0.99 O4(P 0.04 ).
[0089] Comparative Example 1
[0090] This comparative example provides a method for preparing a modified lithium manganese iron phosphate positive electrode material. 1.01 Mn 0.4 Fe 0.6 PO4, and no additional phosphorus source is added in step (3), the rest is the same as in Example 1 and will not be described again.
[0091] Comparative Example 2
[0092] This comparative example provides a method for preparing a modified lithium manganese iron phosphate positive electrode material. 1.01 Mn 0.4 Fe 0.6 Except for PO4, the rest are the same as those in Example 1 and will not be described again.
[0093] Comparative Example 3
[0094] This comparative example provides a method for preparing a modified lithium manganese iron phosphate positive electrode material. The preparation method is the same as Example 2 except that no additional phosphorus source is added in step (3), and will not be described in detail here.
[0095] Comparative Example 4
[0096] This comparative example provides a method for preparing a modified lithium manganese iron phosphate positive electrode material. The preparation method is the same as Example 1 except that no carbon source is added in step (3), and will not be described in detail here.
[0097] Comparative Example 5
[0098] This comparative example provides a method for preparing a modified lithium manganese iron phosphate positive electrode material. 1.01 Mn 0.4 Fe 0.6 Se 0.06 P 0.94 Except for O4, the rest are the same as those in Example 1 and will not be described again.
[0099] Comparative Example 6
[0100] This comparative example provides a method for preparing a modified lithium manganese iron phosphate positive electrode material. 1.01 Mn 0.4 Fe 0.6 Se 0.005 P 0.995 Except for O4, the rest are the same as those in Example 1 and will not be described again.
[0101] Comparative Example 7
[0102] This comparative example provides a method for preparing a modified lithium manganese iron phosphate positive electrode material. 1.01 Mn 0.4 Fe 0.58 Se 0.02 Except for PO4, the rest are the same as those in Example 1 and will not be described again.
[0103] Test method: In order to facilitate comparative experiments, the performance of the lithium-ion positive electrode materials obtained in the above embodiments and comparative examples was tested using the following lithium-ion battery preparation method, which is:
[0104] The above-mentioned lithium manganese iron phosphate composite material was mixed with polyvinylidene fluoride (PVDF) and CNTs (carbon nanotubes) in a mass ratio of 96:3:1, N-methylpyrrolidone (NMP) was used as a solvent to prepare a positive electrode sheet, a metal lithium sheet was used as a counter electrode, a Celgard2400 porous polypropylene film (PP) was used as a separator, the electrolyte was a 1 mol / L lithium hexafluorophosphate (LiPF6) solution, and the solvent was a mixed solution of ethylene carbonate (EC): ethyl carbonate (DMC) in a volume ratio of 1:1. R2032 button batteries were prepared according to a certain assembly process. After completion, they were left to stand for 3 hours to allow the electrolyte and electrode materials to be fully infiltrated.
[0105] Electrochemical performance test: At room temperature (25℃±1), constant current and constant voltage charge and discharge experiments were carried out on Li / Li+ at 1C conditions and in the voltage range of 2.5-4.3V, and the cycles were 500 times.
[0106] PO bond content test: determination of oxidative phosphorylation coupling site.
[0107] Li-O bond content test: FTIR determination.
[0108] Se-O bond content test: ICP-OES method was used for testing.
[0109] FWHM test: measured by X-ray diffractometer.
[0110] Mn dissolution test: ICP-OES method was used for testing.
[0111] Fe dissolution test: ICP-OES method was used for testing.
[0112] Compaction density test: Compaction density meter.
[0113] The test results of the above embodiments and comparative examples are shown in Table 1 and Table 2.
[0114] Table 1
[0115]
[0116] Table 2
[0117]
[0118]
[0119] From Table 1, we can see the following points:
[0120] (1) It can be seen from Examples 1 to 4 that the modified lithium manganese iron phosphate positive electrode material provided by the present invention can avoid the dissolution of Mn and Fe by replacing part of P in the phosphate group with Se and / or Te, and significantly improves the cycle performance of the lithium ion battery, wherein the 1C charging capacity is above 151 mAh / g, the 1C discharge capacity is above 141 mAh / g, and the capacity retention rate after 500 cycles is above 99.9%, which basically does not decrease, and has broad application prospects;
[0121] (2) Combining Examples 1 to 2 and Comparative Examples 1 and 3, it can be seen that the molecular formula A in Comparative Example 1 is Li 1.01 Mn 0.4 Fe 0.6 PO4, and no supplementary phosphorus source is added in step (3), not only the initial discharge capacity decreases to 136.20mAh / g, but also the 1C discharge capacity after 500 cycles decreases to 101.96mAh / g, and the capacity retention rate is only 74.86%, which is significantly lower than that of Example 1 under the same conditions; in step (3) of Comparative Example 3, no supplementary phosphorus source is added, not only the initial discharge capacity decreases to 138.62mAh / g, but also the 1C discharge capacity after 500 cycles decreases to 112.28mAh / g, and the capacity retention rate is only 81.00%, which is significantly lower than that of Example 2 under the same conditions. This shows that the addition of a supplementary phosphorus source is critical to improving the initial discharge capacity and the cycle performance of the battery.
[0122] (3) Based on Example 1, Comparative Example 2, and Comparative Examples 5 to 7, it can be seen that the molecular formula A of Comparative Example 2 is Li 1.01 Mn 0.4 Fe 0.6PO4, that is, without doping Te and / or Se, not only the initial discharge capacity drops to 135.45mAh / g, but also the 1C discharge capacity drops to 108.36mAh / g after 500 cycles, and the capacity retention rate is only 80.00%; in comparative examples 5 to 6, the Se doping amount is too much or too low, resulting in the capacity retention rate dropping to 80.10% and 97.36% respectively after 500 cycles; in comparative example 7, Se is doped in the metal elements instead of replacing the P element, which ultimately leads to limited improvement in the cycle stability, and Mn and Fe are still dissolved. This shows that the present invention replaces part of P with an appropriate amount of Te and / or Se, which has excellent effects of reducing the dissolution of Mn and / or Fe and improving the cycle performance of lithium-ion batteries.
[0123] (4) It can be seen from Example 1 and Comparative Example 4 that no carbon source is added in step (3), resulting in the dissolution of Mn and Fe. After 500 cycles, the capacity retention rate drops to 70.80%, indicating that the present invention has better cycle performance by adding a carbon source in step (3).
[0124] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A modified lithium manganese iron phosphate positive electrode material, characterized in that: The modified lithium manganese iron phosphate positive electrode material comprises a core and a coating layer located on the surface of the core, and the chemical formula of the core comprises Li x Mn y Fe 1-y D z P 1-z O4(P h ), D is selected from Se and / or Te; Among them, 1≤x≤1.05, 0.2≤y≤0.8, 0.01≤z≤0.055, 1.001<1-z+h≤1.
055.
2. The modified lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The particle size D50 of the modified lithium manganese iron phosphate positive electrode material is 90nm to 170nm; Preferably, the average sphericity of the modified lithium manganese iron phosphate positive electrode material is ≥0.80; Preferably, the coating layer is a carbon layer co-doped with P and C; Preferably, the coating layer has a thickness of 0.2 nm to 3 nm; Preferably, the carbon mass content in the modified lithium manganese iron phosphate positive electrode material is 1.4wt% to 1.8wt%; Preferably, the modified lithium manganese iron phosphate positive electrode material includes Se-O bonds and / or Te-O bonds, and the content of the Se-O bonds and / or Te-O bonds is 0.35% to 1.67%; Preferably, the modified lithium manganese iron phosphate positive electrode material includes PO bonds and Li-O bonds, the content of the PO bonds is 36.27% to 38.23%, and the content of the Li-O bonds is 3.1% to 3.3%; Preferably, the full width at half maximum of the X-ray diffraction spectrum of the modified lithium manganese iron phosphate positive electrode material is 0.157 to 0.
179.
3. A method for preparing the modified lithium manganese iron phosphate positive electrode material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) mixing a carbon source, a lithium source, an iron source, a manganese source, a D source and a phosphorus source according to a molar ratio of molecular formula A, grinding and drying to obtain a precursor; molecular formula A is Li x Mn y Fe 1-y D z P 1-z O4, the D source includes a selenium source and / or a tellurium source; wherein 1≤x≤1.05, 0.2≤y≤0.8, 0.01≤z≤0.055; (2) The precursor of step (1) is subjected to a first sintering to obtain a first sample; (3) Mixing a supplementary phosphorus source, a carbon source and the first sample of step (2), and grinding and sintering them in sequence to obtain the modified lithium manganese iron phosphate positive electrode material.
4. The preparation method according to claim 3, characterized in that: The selenium source in step (1) includes any one of selenium dioxide, diselenide dichloride, selenium tetrachloride, selenium oxychloride, sodium selenite, orthoselenide, acid selenide or phenylselenide chloride, or a combination of at least two thereof; Preferably, the tellurium source in step (1) comprises any one of tellurium element powder, sodium tellurite, potassium tellurite, copper telluride, zinc telluride or telluric acid, or a combination of at least two thereof; Preferably, based on the mass of the precursor, the amount of the carbon source added in step (1) is 7 wt% to 9 wt%.
5. The preparation method according to claim 3 or 4, characterized in that: The first sintering includes heating to a first sintering temperature at a first heating rate and performing a first sintering heat preservation; Preferably, the first heating rate is 1°C / min to 5°C / min; Preferably, the first sintering temperature is 300° C. to 500° C.; Preferably, the first sintering and heat-keeping time is 6 hours to 10 hours.
6. The preparation method according to any one of claims 3 to 5, characterized in that: Based on the mass of the first sample, the added amount of the supplementary phosphorus source is 0wt% to 5.5wt%.
7. The preparation method according to any one of claims 3 to 6, characterized in that: Based on the mass of the first sample, the amount of the carbon source added in step (3) is 2 wt% to 3 wt%; Preferably, the carbon source comprises any one of glucose, sucrose or polyethylene glycol, or a combination of at least two of them.
8. The preparation method according to any one of claims 3 to 7, characterized in that: The second sintering includes heating to a second sintering temperature at a second heating rate and performing a second sintering heat preservation; Preferably, the second heating rate is 1°C / min to 10°C / min; Preferably, the second sintering temperature is 600°C to 800°C; Preferably, the second sintering and heat-keeping time is 6 hours to 8 hours.
9. A positive electrode for a lithium ion battery, characterized in that: The lithium-ion battery positive electrode comprises the modified lithium iron manganese phosphate positive electrode material according to claim 1 or 2, and / or the modified lithium iron manganese phosphate positive electrode material prepared by the preparation method of the modified lithium iron manganese phosphate positive electrode material according to any one of claims 3 to 8.
10. A lithium ion battery, characterized in that: The lithium ion battery comprises the lithium ion positive electrode according to claim 9.
Citation Information
Cited By
Multi-layer coated lithium manganese iron phosphate material as well as preparation method and application thereof
CN121269664A